Challenging Our Assumptions: Listening to Refugee and Immigrant Women’s Voices About Career Aspirations - Angela Warner; Dahlia Herring; Lisa E. Baranik; Janice Coles (Journal of Community Engagement and Scholarship)
The St. Vincent de Paul Food Pantry in upstate New York serves refugees and immigrants who have recently arrived in the United States. These newcomers face significant barriers to obtaining economic stability. Those who secure a job usually work in low-paying, entry-level positions such as food service, hospitality, or cleaning. A group of community volunteers and representatives from immigrant-serving agencies was formed to better understand the needs and career aspirations of refugees and immigrants who are served at the food pantry. We conducted three focus groups and one interview with 26 immigrant and refugee women from Afghanistan, Congo-Brazzaville, the Dominican Republic, Iraq, Syria, Trinidad and Tobago, and Ukraine. Participants expressed ambitious career goals such as becoming a lawyer, nurse, judge, police officer, doctor, tailor, and chef. These findings show that community volunteers and representatives should not fall into the trap of low expectations. Instead, we recommend that newcomers’ ambitious career aspirations are heard by community volunteers, that they are given a realistic preview of the work and commitment involved, and that they are provided with resources and support to pursue their desired careers. We share two case studies that highlight the difficult employment barriers that newcomers face as well as career successes from our community. These narratives both illustrate the many challenges faced by newcomers and exemplify how community volunteers can help immigrants overcome these challenges to pursue their career aspirations.